An Efficient Method to Calculate Genomic Prediction Accuracy for New Individuals - Ferdosi, Mohammad H.; Connors, Natalie K.; Tier, Bruce (Frontiers in Genetics, 2019)
Diagonal elements of the coefficient matrix is necessary to calculate the genomic prediction accuracy. Here an improved methodology is described, to update the inverse of the coefficient matrix (C) for new individuals with a genotype, with and without phenotypes. Computational performance is significantly improved by re-using parts of the coefficient matrix inverse calculations that do not change from one animal to another, in combination with updated calculations for those that do change. This method expedites calculation of accuracy for new individuals with genotypes, without re-doing the whole population, by using the previously calculated matrices.